Sound attenuation in the diffusive compressible Euler model (Archives of Mechanics - Test, 2024)
We revisit the diffusive compressible Euler (dcE) model of viscous and heat conducting compressible fluid flow, proposed recently by M. Svärd to supersede the Navier–Stokes–Fourier (NSF) equations. Here, we use acoustic measurements in gases and liquids from the literature to demonstrate that the dcE model fails to describe sound wave attenuation in general fluids with physical accuracy. It is shown, for example, that the dcE model underestimates the sound attenuation coefficients of air and water at room temperature by about 13% and 51%, respectively.